Heating and ultraviolet light activate anti-stress gene functions in humans - Semenkov, Victor F.; Michalski, Anatoli I.; Sapozhnikov, Alexander M. (Frontiers in Genetics, 2015)
All types of cell stress are accompanied by the activation of anti-stress genes that can suppress ROS synthesis. We hypothesized that different environmental factors would affect organisms through the activation of anti-stress genes by autologous serum (AS) proteins, followed by the synthesis of molecules that increase cell resistance to oxidative stress. The goal of this work was to study the influence of AS on ROS production by peripheral blood neutrophils isolated from donors in different age groups. Neutrophils were isolated from 59 donors (38-94 years old). AS was heated at 100˚C for 30 sec. or irradiated by ultraviolet light (UV) at 200-280 nm and 8 W for 10 min. Neutrophils were exposed to heat shock at 42˚C for 1 min. (short-term heating stress) or 43˚C for 10 min., followed by the determination of the chemiluminescence reaction induced by zymosan. AS can increase or decrease ROS production by neutrophils depending on the structure of the proteins in the serum; these structures can be changed by heating or UV treatment and the temperature of their interaction (4˚C or 37˚C). We propose that the effect of environmental factors on AS proteins can cause an adverse increase in oxidative stress levels due to the functional reduction of anti-stress genes. We found a negative correlation between the quantity of intracellular Hsp70 and levels of intracellular ROS production following 10 minutes of heat shock at 43°C. Short-term heating stress (1 minute) at 42°C was followed by a prominent reduction in ROS production. This effect may be a result of the impact of the hormone adrenaline on the functions of anti-stress genes. Indeed, the same effect was observed after treatment of the neutrophils with adrenaline at concentrations of 10-4 M and 10-5 M. In contrast, dexamethasone from the other stress hormone group did not evoke the same effect at the same concentrations.